Product conspicuousness and reference group influence among women: an empirical analysis. (5th July 2019) - Fernandes, Semila Fenelly; Panda, Rajesh
The aim of this study is to investigate reference group influence (RGI) among women across PRN, PRL, PUN and PUL product categories. During product and service purchases, women are more influenced by RGI compared to men as women are more socially connected. The sample size for the study was 1, 044 women from Bengaluru, India. The scale for RGI was developed by Park and Lessig which was partially modified and product conspicuousness paradigm was adopted from Bearden and Etzel. Results of RGI across product categories indicated that IRG was the most universal influence for all four product categories. URG was the most relevant towards PRL while VERG showed significant results towards PUL. RGI within product categories revealed that women rated PRL higher for IRG and URG influences. Additionally, women rated PUL higher for IRG and VERG influences. Post-hoc analysis showed relationship between groups which were significantly different from each other. This resulted in women being important audiences which marketers should not ignore in their advertisements.